Using Precision Prairie Reconstruction to Drive the Native Seeded Species Colonization Process. Issue 4 (7th April 2014) - Grygiel, Carolyn E.; Norland, Jack E.; Biondini, Mario E.
Abstract Restoring forb richness to the northern tallgrass prairie (U.S.A.) is often problematic. A potential solution is the establishment of native forb‐seeded patches that can serve as colonization sites. This study was designed to determine the following: (1) the success at which native forbs sown in small patches can colonize the surrounding vegetation matrix and (2) whether soil amendments (C additions, P fertilization, and seed bank reduction) applied to the seeded sites can facilitate such colonization (patch quality). Colonization was investigated at (1) the immediate surrounding (1 m belt transect, BT) of the seeded sites and (2) in disturbed but not seeded patches located 3 m from the seeded site (out‐plots). Soil amendments did not affect colonization, but native forb density in the BT and out‐plots was correlated to the density of forbs in the seeded sites (r2 = 0.3, p < 0.01). Seeded native forb density in the out‐plots was higher than in the adjacent BT (19 vs. 5 plants/m2), suggesting that competition from the matrix vegetation may be more important in forb colonization than distance from the source. Taller forbs with larger seeds showed advantages in colonization success. This study showed that the colonization of matrix vegetation with native forbs from seeded patches is a viable method for prairie reconstruction but requires the availability of disturbed sites. In most prairies, animal‐generated soil disturbances are common. In their absence, disturbances of the vegetation matrix will need to be added to the management plan.